2016 Anti-doping testing figures (2017)
• A 0.9 percent decrease n the overall number of samples analyzed: 303,369 in 2015 to 300,565 in 2016. • A noteworthy increase in the number of AAFs: 1.26 percent in 2015 (3,809 AAFs from 303,369 samples) to 1.60 percent in 2016 (4,822 AAFs from 300,565 samples). • About 60 percent of WADA-accredited laboratories saw an increase in the total number of samples. • A relative increase in the overall number of (non-Athlete Biological Passport) blood samples analyzed: 6.98 percent in 2015 (21,176 of 303,369) to 7.75 percent in 2016 (23,298 of 300,565). • An increase of 13 percent in the number of ABP samples tested: 25,012 in 2015 to 28,173 in 2016